2020
DOI: 10.1016/j.ceramint.2019.12.199
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonal phase stability maps of ceria-yttria co-doped zirconia: From powders to sintered ceramics

Abstract: Ceria-Yttria co-doped tetragonal zirconia is an attractive class of materials having high strength, toughness and thermal stability. In this study, several co-doped zirconia powders with different stabilizers contents were synthesized via continuous hydrothermal flow synthesis (CHFS). The CHFS was concluded as a suitable method in synthesizing ultrafine tetragonal zirconia particles with controlled morphology. The synthesized powders as well as some commercial powders were heat-treated both in the form of powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Materials in the CeO 2 -Y 2 O 3 -ZrO 2 system have been prepared under solvothermal conditions. Wang et al found that the activation energy of crystal growth is significantly dependent on the CeO 2 concentration [171], and continuous flow synthesis (410 • C, 27 MPa) has been used to form ultrafine stabilised tetragonal zirconia particles [172], while a wide range of nanoscale crystal forms, with intricate morphologies, were possible by inclusion of surfactants, Figure 20 [173]. In the even more complex system ceria-zirconia-yttria-lanthana, high-surface area nanostructured materials have been formed with the aid of lauric acid and dodecylamine [174].…”
Section: Multi-element Substitutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials in the CeO 2 -Y 2 O 3 -ZrO 2 system have been prepared under solvothermal conditions. Wang et al found that the activation energy of crystal growth is significantly dependent on the CeO 2 concentration [171], and continuous flow synthesis (410 • C, 27 MPa) has been used to form ultrafine stabilised tetragonal zirconia particles [172], while a wide range of nanoscale crystal forms, with intricate morphologies, were possible by inclusion of surfactants, Figure 20 [173]. In the even more complex system ceria-zirconia-yttria-lanthana, high-surface area nanostructured materials have been formed with the aid of lauric acid and dodecylamine [174].…”
Section: Multi-element Substitutionsmentioning
confidence: 99%
“…Inorganics 2021, 9, x FOR PEER REVIEW 24 of 35 flow synthesis (410 °C, 27 MPa) has been used to form ultrafine stabilised tetragonal zirconia particles [172], while a wide range of nanoscale crystal forms, with intricate morphologies, were possible by inclusion of surfactants, Figure 20 [173]. In the even more complex system ceria-zirconia-yttria-lanthana, high-surface area nanostructured materials have been formed with the aid of lauric acid and dodecylamine [174].…”
Section: Multi-element Substitutionsmentioning
confidence: 99%
“…In a previous study [30] we developed transformation boundary diagrams for Ce-Y co-doped zirconia, applicable for different temperatures and degrees of powder packing. With this, it is possible to choose the optimum amount of stabilizing agents such that the tetragonal phase has enough stability; yet not being over-stabilized.…”
Section: Introductionmentioning
confidence: 99%
“…With this, it is possible to choose the optimum amount of stabilizing agents such that the tetragonal phase has enough stability; yet not being over-stabilized. It should be noted that the sintering temperature and density of the tetragonal zirconia ceramic are important parameters affecting the stability of the tetragonal phase, and should be considered when choosing the stabilizer concentration [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation